information security handbook - William Caelli (MacMillan Press, 1994)
This book covers the groundby adopting a holistic treatment. It analyses in depth the management controls, both technical and administrative, needed to ensure good levels of security. The first part of the book deals with the non-technical areas of policy formulation, risk management, contingency planning, the law, and auditing. The second half, which builds upon the foundation of the earlier chapters, covers the technical areas of crytography, access control, database security, communication security and security modelling